The impact of mobile applications on the self-care of people with heart failure: a systematic review of the literature - Lopes,Ivo (2021)
Abstract Introduction: Heart failure is a chronic and progressive disease, with high rates of hospital readmission, mortality and morbidity. As a chronic disease, it is essential that people adopt self-care practices to manage their disease more effectively. Digital health technologies, such as mobile applications, can work as facilitators for the self-care of people with heart failure. Objective: Identify the efficacy of mobile applications in the improvement of self-care in people with heart failure. Methods: Systematic review of the literature from the electronic databases - CINAHL Complete, MEDLINE Complete and SciELO carried out in january 2021. Articles published between may 2015 and december 2020 are considered. Results: The research resulted in 67 articles, and 7 of them were included in this review. The use of mobile applications led to improvements in the self-care of the participants from the various studies analysed. Conclusion: The results suggest that the use of mobile applications is effective in improving self-care in cases of heart failure.